2012
DOI: 10.1016/j.ajhg.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A Restricted Spectrum of Mutations in the SMAD4 Tumor-Suppressor Gene Underlies Myhre Syndrome

Abstract: Myhre syndrome is a developmental disorder characterized by reduced growth, generalized muscular hypertrophy, facial dysmorphism, deafness, cognitive deficits, joint stiffness, and skeletal anomalies. Here, by performing exome sequencing of a single affected individual and coupling the results to a hypothesis-driven filtering strategy, we establish that heterozygous mutations in SMAD4, which encodes for a transducer mediating transforming growth factor β and bone morphogenetic protein signaling branches, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 47 publications
6
87
0
Order By: Relevance
“…The mutations were not observed in MS parents, confirming that they occurred de novo. 44 Caputo et al 45 confirmed these results by reporting eight other MS cases with SMAD4 mutations also altering the Ile500 residue.…”
Section: Le Goff and V Cormier-dairesupporting
confidence: 60%
“…The mutations were not observed in MS parents, confirming that they occurred de novo. 44 Caputo et al 45 confirmed these results by reporting eight other MS cases with SMAD4 mutations also altering the Ile500 residue.…”
Section: Le Goff and V Cormier-dairesupporting
confidence: 60%
“…17 All SMAD4 mutations identified occured de novo and no familial transmission has been reported so far. The high average paternal age at birth (436 years), combined with the prevalence of Ile500 change due to mainly two nucleotides changes in SMAD4, may suggest a mechanism of protein-driven selfish selection in sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Le Goff et al 16 identified missense SMAD4 heterozygous mutations, affecting the conserved Ile500 residue as a cause of Myhre syndrome. Shortly after, Caputo et al 17 reported eight other Myhre syndrome cases with SMAD4 mutations altering the Ile500 residue in all their patients. The same mutation was also identified in two patients with LAPS syndrome 18 supporting the concept that Myhre and LAPS syndromes are phenotypic variants of a single entity.…”
Section: Introductionmentioning
confidence: 99%
“…As described below, this subset requires additional screening for these vascular complications. Interestingly, a restricted spectrum of SMAD4 mutations cause Myhre syndrome, defined by developmental and short stature, athletic build, skeletal anomalies, joints stiffness, distinct facial features, and deafness (62).…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%